Worldwide contamination of fish with microplastics: A brief global overview. (November 2020) - Sequeira, Inês F.; Prata, Joana C.; da Costa, João P.; Duarte, Armando C.; Rocha-Santos, Teresa
Abstract: Widespread contamination of microplastics may lead to internalization in fish. This literature review from March 2019 to March 2020 details that a median of 60% of fish, belonging to 198 species captured in 24 countries, contain microplastics in their organs. Carnivores species ingested more microplastics than omnivores. Only 14% of fish were from aquaculture. Most studies focused on digestive systems, with presence in other organs currently being insufficiently assessed. Based on this assessment, knowledge gaps that should be addressed in future studies were identified. Graphical abstract: Unlabelled Image Highlights: Literature review from March 2019 to March 2020 Globally, 60% of fish contained microplastics. No geographical differences in concentrations and fish (%) with microplastics Carnivores had more microplastics than omnivores.